Biden and Latin America. Regional Challenges for US Foreign Policy - Quispe Robles, Javier Luciano (2021)
What are the challenges Joe Biden’s foreign policy faces in Latin America? The American president has promised to open a new era in foreign relations with Latin American countries after four years of Trump’s unilateral and unpredictable foreign policy. However, there are processes underway in Latin America that impose significant constraints for US foreign policy: processes of democratic erosion in several countries of the region, a competitive regional environment led by regional Latin American powers, and a growing presence of China in the region. This article discusses how these processes shape Latin American regional politics and how they challenge the Biden’s broad agenda, ranging from environmental issues, migration, corruption, and human rights. Finally, the article analyzes the engagement of the United States with Latin American countries in light of recent events. Thus, the paper seeks to contribute to the discussion on factors that affect foreign policy and the relationship of the United States with Latin America.